The Implementation of Cognitive and Metacognitive in Speaking Skill through a Short Duration Video to Improve Students’ Confidence - Muhammad Ali Ghufron; Nurmala Hendrawaty (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
Speaking is a productive skill in learning a language, and it is one of the most influential skills that has to be mastered by students in EFL classroom. The improvement of speaking skill is important to the development of the students taking an English Program at university. However, the facts showed that mostly students’ speaking skill is still poor. The problems come up from internal and external factors. From the internal factor, one of the reasons is students feel unconfident to communicate in English both in and outside the classroom, and from the external factor is the monotonous speaking teaching and learning activities in class. To solve the problems, a lecturer requires effective and innovative learning strategies. As a result, the study aims at discussing the implementation of cognitive and metacognitive in speaking skill through a short duration video to improve students’ confidence; in addition, some procedures and considerations are presented in this paper. It can be assumed that implementing both cognitive and metacognitive strategies by watching a short duration video can encourage students’ confidence in speaking skill.